Improving Heat Transfer from Peltier Devices Used in an Atmospheric Water Generation (International Journal of Engineering Materials and Manufacture, 2021)
Present Atmospheric Water Generation (AWG) systems are useful for providing water in areas with limited water supplies. Many industrial AWG systems use VCR (vapor-compression refrigeration) to achieve a large amount of cooling to extract liquid water out of the air.  These systems require large amounts of energy to operate, usually in the form of diesel or AC-powered generators.  The systems also have many moving parts that require maintenance and use refrigerants that can leak and cause problems with the environment. An alternative AWG solution is to use DC-powered Peltier devices (thermoelectric coolers) to reduce the temperature of condensation plates to extract water from the air.  This solution eliminates the issues with traditional industrial AWG systems since the Peltier devices are solid-state, have very long mean-time between failure (MTBF) performance, and can be powered by solar panels that eliminate the need to burn hydrocarbon-based fuels or have access to a reliable power grid.  Also eliminated is the need to use chlorofluorocarbon (CFC) or hydrochlorofluorocarbons (HCFC) refrigerants that have been shown to deplete the ozone layer. This paper will present methods to improve the efficiency of the thermoelectric coolers by more efficiently extracting heat from the hot side of the device.  This efficiency will be quantified by evaluating the coefficient of performance (COP) of the thermoelectric cooler under the various operating conditions.  Different combinations of conductive heat transfer using aluminium heatsinks, convection heat transfer using forced airflow, and phase change heat transfer using copper heat pipes filled with distilled water will be investigated and evaluated.